Maternal Consumption of High-fat Diet in Mice Alters Hypothalamic Notch Pathway, NPY Cell Population and Food Intake in Offspring. (10th February 2018) - Lemes, Simone Ferreira; de Souza, Anelise Cristina Parras; Payolla, Tanyara Baliani; Versutti, Milena Diorio; de Fátima da Silva Ramalho, Albina; Mendes-da-Silva, Cristiano; Souza, Camilla Mendes; Milanski, Marciane; Torsoni, Adriana Souza; Torsoni, Marcio Alberto
Highlights: Maternal HFD consumption during pregnancy and lactation is able to promote long-term metabolic disorders in offspring. HFD exposure in pregnancy and lactation impairs neuronal circuits that control feeding behavior and energy homeostasis. Maternal HFD consumption alters the formation of neurons in the arcuate nucleus, leading to an increase in NPY neurons. Abstract: Studies show that maternal consumption of a high-fat diet (HFD) can impair the formation of hypothalamic neuronal circuits in mouse offspring. This damage can be mediated by Notch1/Hes5 signaling activation, leading to repression of proneural factors such as Mash1 and Ngn2/3, which are essential for neuronal differentiation and neurogenesis. Thus, we aimed to investigate the effects of maternal HFD consumption during gestation and lactation on the Notch1/Mash1 pathway in the hypothalamus and arcuate nucleus (ARC) of mouse offspring (neonates and 28 days old). Our results showed that maternal HFD consumption increases body weight and adiposity of mouse offspring, accompanied by increased levels of Il-1β mRNA compared to those in control offspring. We noticed high mRNA levels of Hes5 accompanied by diminished mRNA levels of Ascl1 (Mash1). The number of Mash1-labeled cells in the ARC was diminished in HFD-O. Additionally, the population of NPY neurons was increased in these animals. Mash1 is important for the development of POMC and NPY neurons in the ARC. Therefore, the reduction in Mash1-labeled cells could be related to modification of the NPY neuron population in the ARC. This scenario favors hyperphagia and weight gain, and could be responsible for the development of obesity in adulthood.